The Study of Continuous Prosperity Problems Based on the Assessment of the Needs of Region's Economy in the Labour Force: According to Panel Surveys of Khabarovsk Krai Employers; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Razumovskaya M. (2016, 2016)
Title screen